HIF-1α Induces HECTD2 Up-Regulation and Aggravates the Malignant Progression of Renal Cell Cancer via Repressing miR-320a - Lv, Dong; Shen, Taimin; Yao, Juncheng; Yang, Qi; Xiang, Ying; Ma, Zhiwei (Frontiers in Cell and Developmental Biology, 2021)
Renal cell carcinoma (RCC) is a frequent malignancy of the urinary system. It has been found that hypoxia mediates the malignant evolvement of RCC. Here, we probe the impact and potential mechanism of HECT domain E3 ubiquitin-protein ligase 2 (HECTD2) and HIF-1α on regulating RCC evolvement. RCC tissues and adjacent normal tissues were collected, and the association between the expression profiles of HECTD2 and HIF-1α and the clinicopathological features was analyzed. Additionally, we constructed HECTD2/HIF-1α overexpression and knockdown models in RCC cell lines to ascertain the impacts of HECTD2 and HIF-1α on RCC cell proliferation, apoptosis, migration, and growth in vivo. We applied bioinformatics to predict the upstream miRNA targets of HECTD2. Meanwhile, RNA immunoprecipitation (RIP), and the dual-luciferase reporter assays were employed to clarify the targeting association between HECTD2 and miR-320a. The effect of miR-320a on HECTD2-mediated RCC progression was investigated. The results suggested that both HIF-1α and HECTD2 were up-regulated in RCC (compared with adjacent non-tumor tissues), and they had positive relationship. Moreover, higher level of HECTD2 and HIF-1α is associated with poorer overall survival of RCC patients. HECTD2 overexpression heightened RCC cell proliferation and migration, and weakened cell apoptosis. On the other hand, the malignant phenotypes of RCC cells were signally impeded by HECTD2 or HIF-1α knockdown. Moreover, miR-320a targeted the 3'-untranslated region of HECTD2 and suppressed HECTD2 expression. The rescue experiments showed that miR-320a restrained HECTD2-mediated malignant progression in RCC, while up-regulation of HIF-1α hampered miR-320a expression. Collectively, HIF-1α mediated HECTD2 up-regulation and aggravated RCC progression by attenuating miR-320a.